2017
DOI: 10.1007/s13246-017-0540-8
|View full text |Cite
|
Sign up to set email alerts
|

Relative biological effectiveness in a proton spread-out Bragg peak formed by pencil beam scanning mode

Abstract: In recent years, there is an increased interest in using scanning modes in proton therapy, due to the more conformal dose distributions, thanks to the spot-weighted dose delivery. The dose rate in each spot is however much higher than the dose rate when using passive irradiation modes, which could affect the cell response. The purpose of this work was to investigate how the relative biological effectiveness changes along the spread-out Bragg peak created by protons delivered by the pencil beam scanning mode. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…The apoptosis level and the number of BNC containing MN have been found to be almost identical for the two modes. In terms of micronuclei frequencies and the 5-Gy-dose point, the frequencies are higher for the peak position in comparison to the proximal position for both modes, which is in agreement with the expected more complex DNA damage at the peak position (see [23]). The micronuclei frequencies appear to be almost the same for the 3-Gy-dose point and slightly higher for PBS for the 5-Gy-dose point, but no statistically significant differences have been found using the t-test in both cases.…”
Section: Discussionsupporting
confidence: 83%
“…The apoptosis level and the number of BNC containing MN have been found to be almost identical for the two modes. In terms of micronuclei frequencies and the 5-Gy-dose point, the frequencies are higher for the peak position in comparison to the proximal position for both modes, which is in agreement with the expected more complex DNA damage at the peak position (see [23]). The micronuclei frequencies appear to be almost the same for the 3-Gy-dose point and slightly higher for PBS for the 5-Gy-dose point, but no statistically significant differences have been found using the t-test in both cases.…”
Section: Discussionsupporting
confidence: 83%
“…The two PBT delivery techniques are currently assumed to be radiobiologically equivalent, with a constant relative biological effectiveness (RBE) of 1.1 [11]. However, a number of preclinical studies have indicated subtle differences between linear energy transfer (LET) and, therefore, RBE, with the two proton delivery techniques, and the clinical relevance of these findings has not been explored [12], [13], [14].…”
Section: Discussionmentioning
confidence: 99%
“…The protons lose energy when hitting the collimator, and their linear energy transfer (LET) increases accordingly. A higher proton LET generates a greater biological effect, as observed in both in vivo and in vitro experiments and even in the clinical outcome . In the previously mentioned study, van Luijk et al estimated the increase of the biological damage based on a simple assumption that the protons with energy above 40 MeV have a relative biological effectiveness (RBE) of 1, while for those below 40 MeV have RBE of 1.2.…”
Section: Introductionmentioning
confidence: 99%